2016
DOI: 10.1002/smll.201602876
|View full text |Cite
|
Sign up to set email alerts
|

Persistency of Enlarged Autolysosomes Underscores Nanoparticle‐Induced Autophagy in Hepatocytes

Abstract: The diverse biological effects of nanomaterials form the basis for their applications in biomedicine but also cause safety issues. Induction of autophagy is a cellular response after nanoparticles exposure. It may be beneficial in some circumstances, yet autophagy-mediated toxicity raises an alarming concern. Previously, it has been reported that upconversion nanoparticles (UCNs) elicit liver damage, with autophagy contributing most of this toxicity. However, the detailed mechanism is unclear. This study revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 49 publications
(54 reference statements)
1
28
0
Order By: Relevance
“…In addition, Stern et al reported that nanoparticles could disrupt the cytoskeleton and prevent lysosomal trafficking, leading to autophagic flux blockage. 1 Moreover, a recent study indicated that upconversion nanoparticles (UCNs) induce autolysosomal membrane turnover anomalies leading to abnormal autophagy [52]. However, the contributions of autophagy initiation and autophagosome synthesis to autophagy dysfunction are rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Stern et al reported that nanoparticles could disrupt the cytoskeleton and prevent lysosomal trafficking, leading to autophagic flux blockage. 1 Moreover, a recent study indicated that upconversion nanoparticles (UCNs) induce autolysosomal membrane turnover anomalies leading to abnormal autophagy [52]. However, the contributions of autophagy initiation and autophagosome synthesis to autophagy dysfunction are rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies confirming that hepatocyte toxicity caused by nanomaterials was mediated by autophagy. (Fan et al, ; Paesano et al, ; Zhang et al, ; Zhu et al, ). Studies have shown that low‐dose (3 μg ml −1 ) CdS QDs can lead to upregulation of autophagy related genes ATG3, ATG7, ATG13 and ATG14, whereas in high doses (14 μg/ml), there is no such inducement effect in HepG2 cells (Paesano et al, ), which suggest the significance of autophagy in preventing intracellular damage.…”
Section: Toxic Effects Of Quantum Dotsmentioning
confidence: 99%
“…There are some studies confirming that hepatocyte toxicity caused by nanomaterials was mediated by autophagy. (Fan et al, 2016;Paesano et al, 2016;Zhang et al, 2017;Zhu et al, 2017). Studies have shown that low-dose (3 μg ml −1 ) CdS QDs can lead to upregulation of autophagy related genes ATG3, ATG7, ATG13 and ATG14, whereas in high doses (14 μg/ml),…”
Section: Elevated Intracellular Ca 2+ Levelsmentioning
confidence: 99%
“…Trehalose and CQ are commonly used as an autophagy inducer and blocker, respectively [18,23]. Trehalose significantly attenuated the elevation of GFP-Htt (Q74) puncta following midazolam treatment, but CQ had the opposite effect (Fig.…”
Section: Role Of Autophagy In Midazolam-induced Gfp-htt (Q74) Accumulmentioning
confidence: 99%
“…3c) suggested the blockade of autophagic flux [23,29]; thus, we measured autophagic degradation. The effect of sequestosome 1 (SQSTM1/p62), a protein substrate that is selectively incorporated during the formation of autophagosomes and degraded by autophagy, was investigated first [30].…”
Section: Midazolam Impaired Autophagic Degradationmentioning
confidence: 99%